Comparative study of leaf anatomy and micromorphology of selected Justicia species from Peninsular Malaysia - Aidatul Aifa Mohd Tajudin; Che Nurul Aini Che Amri; Rozilawati Shahari (Penerbit Universiti Kebangsaan Malaysia, 2022)
Justicia has been recognized as one of the largest genera in the Acanthaceae family with 600 species have been identified. Most researchers have problems identifying Justicia species especially if the samples are incomplete. Other than that, there is no comprehensive study on Justicia species, especially in Peninsular Malaysia. Therefore, a comprehensive study of leaf anatomy and micromorphology of three selected Justicia species which are Justicia adathoda, Justicia gendarussa and Justicia procumbens were conducted in order to assess the leaf anatomical and micromorphological variations that would be useful to identify the plant species. The methods used in this study involved several methods such as cross-section using a sliding microtome and observation under the scanning electron microscope (SEM) for the epidermis of abaxial and adaxial surfaces. Collenchyma, sclerenchyma and mucilage cells can be found either in the petiole or the midrib in all species studied. Amphistomatic stomata have also been recorded in all species examined. Meanwhile, several differences were discovered in this study, including the type of trichomes, the pattern of vascular bundles, the type of epicuticular wax structures, cuticle ornamentation and the presence of cystolith cells. In conclusion, the characteristics of some Justicia species in Peninsular Malaysia can be identified using leaf anatomy and micromorphology.